OP27 Implementation of the serious illness care programin the hospital setting: emerging results of a multi-site quality improvement collaborative. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Simon, J; Semenchuk, J; Dunne, F; Ma, I; Singh, J; Swinton, M; Jayaraman, D; Lagrotteria, A; You, J
Abstract : Background: Seriously ill, hospitalized patients often receive treatment that is not aligned with their values and goals. The Serious Illness Care Program (SICP) is a multi-faceted health system intervention aimed at enabling more person-centered conversations about goals-of-care (GoC) with patients who have serious, life-limiting illness. Methods: We conducted a multi-site quality improvement study to adapt and implement the SICP on the medical wards of 3 Canadian hospitals. Our primary outcome measure was the change in patient or family member responses to the validated question: "Over the past 2 days, how much have you felt heard and understood?" (1=not at all; 5=completely) before versus after a conversation about GoC with a clinician trained in the use of the Serious Illness Conversation Guide (SICG). At one site, we also examined health resource use before and after implementation. Results: With phased implementation across sites, we trained 57 clinicians in use of the SICG, delivered conversations using the SICG to 205 patients (mean age 76 years), or their family members. Of these conversations, 139 were documented in the electronic medical record. After these guided conversations, participants felt more heard and understood (increase of 0.4 ± 1.1 points; P=0.005). Compared to historical controls, conversations using the SICG were associated with a reduction in length of stay as an acute care patient (5 vs. 19 days, P=0.001). Conclusion: The SICP was associated with improvement in patients' and family members' perception of being heard and understood by their healthcare team and a reduction in health resource use.